Electrostatic interactions modulate the differential aggregation propensities of IgG1 and IgG4P antibodies and inform charged residue substitutions for improved developability. Issue 6 (23rd December 2019) - Heads, James T; Lamb, Richard; Kelm, Sebastian; Adams, Ralph; Elliott, Peter; Tyson, Kerry; Topia, Sarfaraj; West, Shauna; Nan, Ruodan; Turner, Alison; Lawson, Alastair D G
Abstract: Native state aggregation is an important concern in the development of therapeutic antibodies. Enhanced knowledge of mAb native state aggregation mechanisms would permit sequence-based selection and design of therapeutic mAbs with improved developability. We investigated how electrostatic interactions affect the native state aggregation of seven human IgG1 and IgG4P mAb isotype pairs, each pair having identical variable domains that are different for each set of IgG1 and IgG4P constructs. Relative aggregation propensities were determined at pH 7.4, representing physiological conditions, and pH 5.0, representing commonly used storage conditions. Our work indicates that the net charge state of variable domains relative to the net charge state of the constant domains is predominantly responsible for the different native state aggregation behavior of IgG1 and IgG4P mAbs. This observation suggests that the global net charge of a multi domain protein is not a reliable predictor of aggregation propensity. Furthermore, we demonstrate a design strategy in the frameworks of variable domains to reduce the native state aggregation propensity of mAbs identified as being aggregation-prone. Importantly, substitution of specifically identified residues with alternative, human germline residues, to optimize Fv charge, resulted in decreased aggregation potential at pH 5.0 and 7.4, thus increasing developability.